Description of the Characteristics of Mothers with Premature Rupture of Membrane: Gambaran Karakteristik Ibu Bersalin dengan Ketuban Pecah Dini - Nilda Yulita Siregar; Orizza Varian Indah; Lisda Widianti Longgupa; Fransisca Noya; Sony Bernike Magdalena Sitorus; Nurfatimah Nurfatimah (Poltekkes Kemenkes Palu, 2023)
Background: The incidence of premature rupture of membranes (PROM) ranges from 3-18% in preterm pregnancies, while in term pregnancies it is around 8-10%. PROM case data at the Poso Regional General Hospital (RSUD) from 2017 to 2020 has fluctuated. In 2017 there were 534 cases, in 2018 there were 452 cases and in 2019 there were 773 cases.Objective: This study was to describe the characteristics of mothers giving birth with PROM at Poso Hospital. Methods: Descriptive by using secondary data. The sample size was 142 pregnant women who experienced premature rupture of membranes in 2020 at Poso Hospital using the total sampling technique. Data were analyzed by univariate test. Results: The highest distribution of PROM incidence was in mothers aged 20-35 years, based on parity, the highest were multiparas, and the highest was based on work, namely mothers who did not work suggestions for the Poso Hospital, especially for medical record officers to complete patient data thoroughly.